Adar RNA editing-dependent and -independent effects are required for brain and innate immune functions in Drosophila - Deng, Patricia; Khan, Anzer; Jacobson, Dionna; Sambrani, Nagraj; McGurk, Leeanne; Li, Xianghua; Jayasree, Aswathy; Hejatko, Jan; Shohat-Ophir, Galit; O'Connell, Mary A; Li, Jin Billy; Keegan, Liam P (Nature communications, 2020)
ADAR RNA editing enzymes are high-affinity dsRNA-binding proteins that deaminate adenosines to inosines in pre-mRNA hairpins and also exert editing-independent effects. We generated a Drosophila AdarE374A mutant strain encoding a catalytically inactive Adar with CRISPR/Cas9. We demonstrate that Adar adenosine deamination activity is necessary for normal locomotion and prevents age-dependent neurodegeneration. The catalytically inactive protein, when expressed at a higher than physiological level, can rescue neurodegeneration in Adar mutants, suggesting also editing-independent effects. Furthermore, loss of Adar RNA editing activity leads to innate immune induction, indicating that Drosophila Adar, despite being the homolog of mammalian ADAR2, also has functions similar to mammalian ADAR1. The innate immune induction in fly Adar mutants is suppressed by silencing of Dicer-2, which has a RNA helicase domain similar to MDA5 that senses unedited dsRNAs in mammalian Adar1 mutants. Our work demonstrates that the single Adar enzyme in Drosophila unexpectedly has dual functions.
Keywords: degenerace nervu; přirozená imunita; proteiny Drosophily; editace RNA; Adenosine Deaminase; Drosophila melanogaster; Gene Expression Regulation; Point Mutation; stárnutí; Adenosine Monophosphate; messenger RNA; RNA, Messenger; RNA Editing; Immunity, Innate; Drosophila Proteins; Ribonuclease III; Protein Domains; RNA Helicases; adenosindeaminasa; adenosinmonofosfát; Catalysis; katalýza; Nerve Degeneration; lokomoce; ribonukleasa III; zvířata; Aging; Animals; mozek; Brain; proteinové domény; Locomotion; regulace genové exprese; RNA-helikasy; bodová mutace